Research progress of targeted therapy combined with immunotherapy for hepatocellular carcinoma - Xie, Shuqi; Wang, Mengchao; Zeng, Chuanxiu; Ou, Yan; Zhao, Lu; Wang, Dong; Chen, Liwei; Kong, Fanming; Yi, Dan (Frontiers in Oncology, 2023)
Hepatocellular carcinoma is a common gastrointestinal malignancy with a high mortality rate and limited treatment options. Molecularly targeted drugs combined with immune checkpoint inhibitors have shown unique advantages over single agent applications, significantly prolonging patient survival and bringing hope to patients. This paper reviews the research progress of molecular targeted drugs combined with immune checkpoint inhibitors in the treatment of hepatocellular carcinoma, and discusses the effectiveness and safety of the combination of the two drugs to provide reference for the further application of molecular targeted drugs combined with immune checkpoint inhibitors in clinical practice.